2013
DOI: 10.2174/187221313804004682
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Allergy and Asthma, Complex Immune Origin Diseases: Mechanisms and Therapeutic Agents

Abstract: Inflammation, allergy and asthma are the manifestation of multitude reactions of biological, cellular and immunological events. The various associated biological, cellular, and molecular events with inflammation, allergy and asthma participate to induce increased vascular permeability, vasodilatation, cellular migration, increased mucus secretion, broncho-constriction, structural changes of airway architecture, decline in pulmonary functions, release of intracellular mediators, increased formation of reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 154 publications
1
21
0
2
Order By: Relevance
“…Evidence has indicated that chronic inflammatory processes in asthma and liver cirrhosis, like the pathophysiology of RA, involve cytokine interactions [29][31], and this combined and augmented chronic inflammatory effect might subsequently induce bipolar disorder. Moreover, cytokines that potentially cause depression and anxiety in liver cirrhosis [32] might also be associated with the development of bipolar disorder [33].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated that chronic inflammatory processes in asthma and liver cirrhosis, like the pathophysiology of RA, involve cytokine interactions [29][31], and this combined and augmented chronic inflammatory effect might subsequently induce bipolar disorder. Moreover, cytokines that potentially cause depression and anxiety in liver cirrhosis [32] might also be associated with the development of bipolar disorder [33].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 3 4 ] Increased expression of these proinflammatory cytokines and various chemokines, at mRNA or protein levels, is observed in different clinical samples of asthmatics compared with controls, such as peripheral blood, sputum, bronchoalveolar lavage fluid (BALF), and bronchial biopsies. [ 5 6 7 8 ] However, these observations vary from individual studies and sometimes are even contradictory, possibly because of the limitation of numbers of subjects, different kinds of samples, and noncorrespondence between transcription and translation of certain molecules. In this case, little is known about the systemic evaluation of whether these proinflammatory cytokines and chemokines are all equally important and what is the associated status of other biomarkers in human asthmatic airways.…”
Section: Introductionmentioning
confidence: 99%
“…Leucocyte infiltration induces mucosal tissue damage in colons, resulting in an inflammatory response involving cytokines and the chemokine MCP-1 [15]. Anticolitis medications such as sulfasalazine significantly decrease colitis and neutrophil/macrophage infiltration by reducing cytokine and chemokine levels [16, 17]. Polyphenol-rich extra-virgin olive oil has been shown to modulate macrophage activation and decrease cytokine production in UC [18].…”
Section: Discussionmentioning
confidence: 99%